2018
DOI: 10.3389/fimmu.2018.02679
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding Class Switch Recombination-Related Transcription in Human Normal and Pathological Immune Responses

Abstract: Antibody class switch recombination (CSR) to IgG, IgA, or IgE is a hallmark of adaptive immunity, allowing antibody function diversification beyond IgM. CSR involves a deletion of the IgM/IgD constant region genes placing a new acceptor Constant gene, downstream of the VDJH exon. CSR depends on non-coding (CSRnc) transcription of donor Iμ and acceptor IH exons, located 5′ upstream of each CH coding gene. Although, our knowledge of the role of CSRnc transcription has advanced greatly, its extension and importan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…The interchromosomal translocation analysis with our original CTX-explorer software (see Material and methods for details), followed by PCR and Sanger sequencing, showed that the breakpoint on chromosome 8 was located 158 kb downstream of 3′ MYC , in the PVT1 region (chr8:127,901,209) (Figs 4 and 5 ). Regarding the breakpoint on chromosome 14, it was between joining and constant IGH regions, 1.6 kb upstream of the Sμ switch region (ch14:105,862,125), according to the recently mapped IGH switch regions (Sμ: 105,856,501–105,860,500) ( S1A Fig ) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The interchromosomal translocation analysis with our original CTX-explorer software (see Material and methods for details), followed by PCR and Sanger sequencing, showed that the breakpoint on chromosome 8 was located 158 kb downstream of 3′ MYC , in the PVT1 region (chr8:127,901,209) (Figs 4 and 5 ). Regarding the breakpoint on chromosome 14, it was between joining and constant IGH regions, 1.6 kb upstream of the Sμ switch region (ch14:105,862,125), according to the recently mapped IGH switch regions (Sμ: 105,856,501–105,860,500) ( S1A Fig ) [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The TME risk prognostic model also included immune-related genes (KLRB1 and IGHD). Proteins coded by these genes were associated with the immune microenvironment ( 52 ) and immune cell infiltration ( 53 ) (such as natural killer cells and T cells). In our study, the low-TME-risk group upregulated in many immune checkpoints and increased in most of the immune and stromal cells, including B cells, T cells CD4+, T cells CD8+, and myeloid dendritic cells.…”
Section: Discussionmentioning
confidence: 99%